Pengawasan Dewan Perwakilan Rakyat Daerah Terhadap Pelaksanaan Anggaran Pendapatan Belanja Daerah di Kabupaten Mamuju - Faradillah Paratama; Arif Maulana; Jamil Resa; Anjeliana Nafsia (Fakultas Hukum, Universitas Sawerigading Makassar, 2025)
As part of the regional government, the Regency/Municipal Regional People’s Representative Council (DPRD) has functions, duties, and authorities. Article 149 paragraph (1) of Law Number 23 of 2014 states that the Regency/Municipal DPRD has the function of forming regency/municipal regional regulations, the budgeting function, and the supervisory function. As representatives of the people, the DPRD has three functions, namely legislation, budgeting, and supervision. Misuse of the Regional Revenue and Expenditure Budget (APBD) frequently occurs in local governments. The APBD managed by regional governments is vulnerable to misuse, including for the personal interests of regional heads. The purpose of this research is to identify and analyze how the DPRD supervises the implementation of the Regional Revenue and Expenditure Budget in Mamuju Regency. The research method used by the author is normative juridical research, which focuses on law as norms, rules, legal principles, legal doctrines, legal theories, and other legal literature to address the legal issues under study. The results of the research indicate that the supervision carried out by the DPRD over the implementation of the APBD in Mamuju Regency faces several obstacles. These obstacles are caused by various factors, including the quality of DPRD members (human resources), such as the level of formal education, knowledge, experience, leadership, expertise, and capabilities of the members. Educational background is an essential factor in determining the quality or competence of a DPRD member. In addition, there is a lack of communication between DPRD members and the community, as well as relatively low public political awareness